MÉXICO E SANTA FÉ - MURAIS NAS CORES FICCIONAIS DE ERICO VERÃ?SSIMO (Letras & Letras, 2007)
ABSTRACT: This essay is on the thematic relationship found between the work of the Mexican muralists and the books: O Tempo e o Vento, Noite, and México by the Brazilian writer Erico Verissimo. México (1957) is the point of reference to this discussion, because it shows the knowledge of the author about the country, about its politics, art and history, calling the attention to the muralists' thematic work and its link with O Tempo e o Vento e Noite. The trip report adopted is the form the author developed to reactivate the Brazilian political and social reality exposed initially in O Continente (1949). This relationship is reinforced with the "conceptualizationâ€? of the "ancient horrorâ€? and that of the "modern horrorâ€? by the writer-protagonist, Floriano Terra Cambará, on the last pages of O Retrato (1951). This conception has some points of reference with the predominant concepts found in the work of the Mexican muralists.